Asymmetric Mannich/Cyclization Reaction of 2-Benzothiazolimines and 2-Isothiocyano-1-indanones to Construct Chiral Spirocyclic Compounds - Yao Zheng; Da-Ming Du (Molecules, 2024)
An efficient and practical organocatalyzed asymmetric Mannich/cyclization tandem reaction strategy of 2-benzothiazolimines and 2-isothiocyanato-1-indanones was developed, and novel spirocyclic compounds containing benzothiazolimine and indanone scaffolds were obtained. This chiral thiourea-catalyzed Mannich/cyclization tandem reaction offers chiral spirocyclic compounds with continuous tertiary and quaternary stereocenters in good to high yields (up to 90%) with excellent diastereoselectivities (up to >20:1 dr) and enantioselectivities (up to 98% ee) at −18 °C. Additionally, the scaled-up synthesis was also performed with retained yield and stereoselectivity, and a reaction mechanism was also proposed.